The Diary of Emma Simpson : When Will this Cruel War Be Over? - Denenberg, Barry (SCHOLASTIC INC., 1996)
The peaceful, traditional Southern life that Emma Simpson and her family know is shattered when the Civil War reaches their soil. Soon, Emma's father and brother are called to battle, but her family is confident that the South will quickly win the War between the States. As the months drag on, though, the harsh realities of war set in. Death and hardship are all around, and food, medicine, firewood, and ink for Emma to write in her diary become increasingly scarce as troops from the North march deeper into the South. Eventually, even Emma's home is commandeered by the Yankees, Still, with a brave spirit and the knowledge of what is most important in life, Emma never loses hope that the war will end.